2021
DOI: 10.1080/02827581.2021.1908591
|View full text |Cite
|
Sign up to set email alerts
|

Modelling effects of regeneration method on the growth and profitability of Scots pine stands

Abstract: Despite numerous studies there are still uncertainties regarding regeneration strategies that are optimal for productivity and profitability. Thus the aim of this study was to establish effects of three regeneration methods (planting, direct seeding and natural regeneration) on the production and profitability of Scots pine (Pinus sylvestris L.) stands in southern Sweden. Long-term stand development was simulated, with the StandWise application of the Heureka decision support system, starting from short-term r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…As the core of the system concerns the development of the tree layer, it has frequently been used for examining the effect of different management systems or silvicultural actions on timber production. Examples include assessments of continuous cover versus clearcut forestry (Nordström et al, 2013;Lundmark et al, 2016), regeneration efforts (Lula et al, 2021;Jonsson et al, 2022) and pre-commercial thinning (Fahlvik et al, 2015(Fahlvik et al, , 2017Holmström et al, 2016). As above and below ground biomass is calculated in the system, several studies have assessed bioenergy potentials (Snäll et al, 2017;Eggers et al, 2020a), carbon sequestration as well as the combination of these two aspects (Cintas et al, 2017).…”
Section: Application Within Researchmentioning
confidence: 99%
“…As the core of the system concerns the development of the tree layer, it has frequently been used for examining the effect of different management systems or silvicultural actions on timber production. Examples include assessments of continuous cover versus clearcut forestry (Nordström et al, 2013;Lundmark et al, 2016), regeneration efforts (Lula et al, 2021;Jonsson et al, 2022) and pre-commercial thinning (Fahlvik et al, 2015(Fahlvik et al, , 2017Holmström et al, 2016). As above and below ground biomass is calculated in the system, several studies have assessed bioenergy potentials (Snäll et al, 2017;Eggers et al, 2020a), carbon sequestration as well as the combination of these two aspects (Cintas et al, 2017).…”
Section: Application Within Researchmentioning
confidence: 99%
“…www.forest-journal.com Lula et al (2021) analyzed the profitability of Scots pine stands in southern Sweden and found that highdensity planting (10,000 seedlings per hectare) resulted in a negative LEV, while planting on clear-cuts with 1,600 -3,265 seedlings per hectare resulted in the highest profitability and production. The negative LEV for high-density planting confirms our results.…”
Section: Wwwforest-journalcommentioning
confidence: 99%
“…Biological (ecophysiological, genetic, etc. )-study of the ontogenesis of seedlings, the influence of external factors on young forest stands, biomass accumulation [11,[63][64][65][66][67][68][69], and patterns between phenotypic and genetic variations of forest trees [70]; 3.…”
Section: Interpretation An Flr Algorithmmentioning
confidence: 99%